2019
DOI: 10.21203/rs.2.14781/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Determinants of precancerous cervical lesion among women screened for cervical cancer in south Ethiopia: A case-control study

Abstract: Background Nearly 90% of deaths from cervical cancer occurred in low resource setting. In Ethiopia the magnitude of cervical cancer was 17%. Precancerous cervical lesions may progress to cervical cancer. Early screening and treatment of precancerous cervical lesions is a cost effective way to avert the growth of cervical cancer. However, there is a limited research on risk factors of precancerous cervical lesions in Ethiopia. Therefore the aim of this study was to identify determinants of precancerous cervical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
0
1
Order By: Relevance
“…About 232 (68.2%) respondents had their first sexual intercourse aged <18 years; however, there was no significant association between age at first sex and precancerous cervical lesions. Our finding contradict other studies done in different settings, 12 , 34–37 which showed that early initiation of sexual intercourse was significantly associated with developing precancerous cervical lesions. This discrepancy may be due to failure to remember age at first sex.…”
Section: Discussioncontrasting
confidence: 99%
“…About 232 (68.2%) respondents had their first sexual intercourse aged <18 years; however, there was no significant association between age at first sex and precancerous cervical lesions. Our finding contradict other studies done in different settings, 12 , 34–37 which showed that early initiation of sexual intercourse was significantly associated with developing precancerous cervical lesions. This discrepancy may be due to failure to remember age at first sex.…”
Section: Discussioncontrasting
confidence: 99%